Morphology of lymphoid nodules and aggregates in the lungs of calves at different ages - Saw, Po Po; Abu Bakar @ Zakaria, Md Zuki; Saad, Mohd Zamri (Veterinary Association Malaysia, 2009)
The present study was conducted with the aim of defining the morphology of lymphoid nodules and lymphoid aggregates in calves at different ages. A total of 9 calves, divided into 3 age groups (3-, 6- and 8-month-old) consisting of 3 calves in each group, was used in this study. Samples of the lungs were taken systematically and processed for histological examinations. The tissues were sectioned at 4, μm, stained with Haematoxylin and Eosin and examined under light microscope. The occurrence and structure of lymphoid nodules and lymphoid aggregates varied between the age groups. The number of lymphoid nodules and lymphoid aggregates in the lung of calves increased with age. The number of lymphoid nodules and lymphoid aggregates in the 8-month-old calves was significantly higher (P<0.05) than in the 3- and 6-month-old calves. Similarly, the size of lymphoid nodule and lymphoid aggregates increased with age and was significantly higher (P<0.05) in the 8-month-old calves as compared to the 3- and 6- month-old calves. The number of intraepithelial lymphocytes (IELs) within the lymphoid nodules and lymphoid aggregates was significantly higher (P<0.05) in the 8-month-old calves compared to the 3- and 6-month-old calves.